Stress-induced selective nano-crystallization in laser-processed amorphous Fe-Si-B alloys - Katakam, Shravana; Santhanakrishnan, S.; Vora, Hitesh; Hwang, Jun Y.; Banerjee, Rajarshi; Dahotre, Narendra B. (TAYLOR & FRANCIS LTD, 2012)
It is shown that laser processing results in localized compressive stresses in amorphous Fe-Si-B, leading to homogeneous nano-crystallization at the edges of the laser track. The mechanism can be attributed to enhanced diffusivity at these edges, resulting from a reduced diffusion activation barrier, which has been calculated by coupling the results of a thermal model with microstructural characterization.
Keywords: NANOCRYSTALLIZATION; TEMPERATURE